2015
DOI: 10.1088/0004-637x/805/2/168
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends of Cme Deflections Based on Cme and Solar Parameters

Abstract: Accurate space weather forecasting requires knowledge of the trajectory of coronal mass ejections (CMEs), including any deflections close to the Sun or through interplanetary space. Kay et al. (2013) introduced ForeCAT, a model of CME deflection resulting from the background solar magnetic field. For a magnetic field solution corresponding to Carrington Rotation (CR) 2029 (declining phase, April-May 2005), the majority of the CMEs deflected to the Heliospheric Current Sheet (HCS), the minimum in magnetic press… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 74 publications
9
111
0
Order By: Relevance
“…From previous works, CME trajectories are deflected mainly in the low corona (until ∼5 R  ), where the magnetic gradients are the strongest (Kay et al 2013(Kay et al , 2015b. In agreement with theliterature, CME trajectories simulated with ForeCAT deflect toward the heliospheric current sheet (HCS) and away from coronal holes (Cremades & Bothmer 2004;Gopalswamy et al 2009a;Kilpua et al 2009).…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…From previous works, CME trajectories are deflected mainly in the low corona (until ∼5 R  ), where the magnetic gradients are the strongest (Kay et al 2013(Kay et al , 2015b. In agreement with theliterature, CME trajectories simulated with ForeCAT deflect toward the heliospheric current sheet (HCS) and away from coronal holes (Cremades & Bothmer 2004;Gopalswamy et al 2009a;Kilpua et al 2009).…”
Section: Introductionsupporting
confidence: 79%
“…One set of parameters defines the CME shape. The CME flux rope is assumed to have a toroidal shape (Figure 2 in Kay et al 2015b): a and c describe the height and width of the CME, b represents the thickness, and d is the center of the CME's toroidal axis above the surface of the Sun. Since the first data point in the Landi et al (2010) SOHO and STEREO-A data set is so close to the Sun's surface (R 0 =1.1 R  ), we consider the initial CME nose position to bea + b + d=R 0 .…”
Section: Comparison With Forecatmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous coronagraph observations suggested that latitudinal deflections of CMEs were controlled by the background coronal magnetic field and the overall flow near solar minimum (MacQueen et al 1986), which was confirmed by the result that CMEs near solar minimum were systematically deflected toward lower latitudes while CMEs during solar maximum could deviate toward either the pole or equator (e.g., Cremades & Bothmer 2004;Kilpua et al 2009). Some CMEs were found to be deflected toward the weak magnetic field region associated with the streamer belt or the heliospheric current sheet (e.g., Xie et al 2009;Kay et al 2013;Liewer et al 2015), while Xie et al (2009) reported that fast CMEs could be deflected away from the streamer belt. The coronal hole with strong open magnetic field is one important factor that can divert a CME (e.g., Gopalswamy et al 2004Gopalswamy et al , 2005Gopalswamy et al , 2009Xie et al 2009;Panasenco et al 2013).…”
Section: Introductionmentioning
confidence: 99%